Sialorrhoea associated with sertraline use. Issue 4 (November 2019) - Şahan, Ebru; Kılıçarslan, Tezer; Kırpınar, İsmet
Introduction: Sialorrhoea, which has been defined as excessive amount of saliva in the mouth, can be a debilitating symptom. Psychoactive drugs may cause an increase or decrease in saliva secretion. Antidepressant drugs, especially tricyclic antidepressants and less often serotonin reuptake inhibitors, are often associated with a decrease in salivation and the complaint of dry mouth. Case presentation: A 46-year-old male patient with complaints of being depressed, lack of motivation, irritability and difficulty in falling asleep was started on sertraline treatment and had trouble with sialorrhoea after the dose increase, without other causes of hypersalivation. Discussion: We could not find report of any case with antidepressant-associated sialorrhoea in the literature. Future cases may support a relationship between sertraline and sialorrhoea.